Factors Affecting The Development of The Kopra Industry: A Case Study of Konawe Kepulauan District – Southeast Sulawesi - Dhian Herdhiansyah; Ardhiansyah; La Rianda; Asriani (Universitas Djuanda, 2021)
This study aims to determine: (a) copra processing technology, and (b) factors that influence the development of the copra industry. The location of this research was carried out in Konawe Islands Regency, Southeast Sulawesi Province. Research variables include labor wages, raw materials, income, copra production, capital, equipment, and depreciation of copra prices, and copra processing revenue. The results showed that: copra processing includes: (a) picking, (b) transportation, (c) stripping, (d) cleavage, (d) gouging, and (e) drying. Factors that influence the development of the copra industry: Factors that influence the development of the copra industry: (a) labor factor (X1) shows a regression coefficient of -0.138 and a significant value of 0.112> 0.1; (b) the business capital factor (X2) shows the regression coefficient value of 0.017 and a significant value of 0.252> 0.1, and (c) the raw material factor (X3) shows the regression coefficient value of 0.245 and a significant value of 0.000 <0.1.